By the Book or Out of the Box? Top Decision Maker Cognitive Style, Gender, and Firm Absorptive Capacity - Pryor, Christopher; Hirth, Robert; Jin, Yanghua (Frontiers in Psychology, 2021)
Despite scholars’ early emphasis on the role people play in fostering firms’ absorptive capacity, research has not deeply explored the individual-level antecedents of this important capability. We draw on adaptive-innovative theory to explain how top decision makers’ cognitive styles can influence the degree to which their firms develop absorptive capacity. Top decision makers who have high adaptive cognitive style prefer to adhere to existing norms, follow established procedures, and rely on current knowledge, and we argue that these attributes will strengthen those dimensions of absorptive capacity based on firms’ existing knowledge and knowledge-assimilation abilities. Top decision makers who have high innovative cognitive style are more likely to reframe information, experiment with new problem-solving approaches, and take risks by violating norms, and we argue that these attributes may strengthen those dimensions of absorptive capacity based on firms’ acquisition of new knowledge and the assimilation of knowledge throughout the firm. We also argue that gender differences may moderate these effects. Empirical results support our hypotheses.